Combined Vertebral Fracture Assessment and FRAX Tool Thailand With or Without Bone Mineral Density for Diagnosis of Osteoporosis in Elderly - Kijparkorn, Supakrit; Wanichtanom, Nongworapat; Sueajui, Jithayut (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: To evaluate the reliability of using vertebral fracture assessment by radiography (VFA) in combination with FRAX tool Thailand to diagnose osteoporosis in elderly patients, without the need for bone mineral density (BMD) measurement. Methods: All elderly individuals who fulfill the criteria for osteoporosis assessment according to the 2021 CPG for osteoporosis care by the Thailand osteoporosis foundation were assessed BMD, VFA, and FRAX tool Thailand with and without BMD. Fracture risk was first evaluated using only FRAX without BMD and the presence of asymptomatic vertebral fractures (AVF). The second assessment used FRAX with BMD, the results of BMD measurements, and the presence of AVF. The results of these two assessments were compared to evaluate the reliability of the osteoporotic diagnosis. Results: The prevalence of osteoporosis in the study was found to be 67% (95% CI: 60%–72.9%). The test exhibited high sensitivity (90.6%, 95% CI: 84.5%–94.9%) and specificity (92.9%, 95% CI: 84.1%–97.6%), indicating its strong ability to accurately identify both individuals with and without osteoporosis. The Receiver Operating Characteristic (ROC) area of 0.918 (95% CI: 0.879–0.956). For subgroup analysis, in males (n=44), the test demonstrated excellent performance with a sensitivity of 95.2%, specificity of 100%, and a sensitivity of 89.8% and specificity of 89.4% in females (n=165). In the age-based subgroup analysis, the results in those aged >80 years (n=35) had highest sensitivity at 96.8% but lower specificity at 75.0%. For participants aged 70-80 years (n=84), sensitivity was 94.7%, and specificity was 88.9%. The youngest group, aged <70 years (n=90), had the lowest sensitivity of 82.4% but a high specificity of 97.4%. The ROC area ranged from 0.85 in those >80 years, 0.89 in those <70 years, and 0.91 in the aged 70-80 years group. Conclusions: The combined use of VFA and FRAX without BMD offers a simple, highly effective method for diagnosing osteoporosis in elderly patients, especially in all men and women aged 70-80 years at minimal cost.